Simultaneous multi-signal quantification for highly precise serodiagnosis utilizing a rationally constructed platform - Yuxin Liu (Nature Portfolio, 2019)
Single channel detection methods often suffer from false positives when analysing biological samples. Here, the authors report on the development of a three-channel detection device for measuring hydrogen sulphide in serum and demonstrate application in an in vivo model.